Ketercapaian pembelajaran membaca berbasis teks oleh peserta didik kelas VIII SMP Global Surya Bandar Lampung - Suyanto, Edi; Ariyani, Farida; Prayodi, Rahmat (Aksara: Jurnal Bahasa dan Sastra, 2023)
The low reading ability is one of the causes of reading strategies that are less acceptable. The impact of the lack of acceptance of the strategy used will have a negative impact on students' comprehension of reading content. Therefore, this study aims to describe the achievement of text-based reading learning, which focuses on the aspects of building text, modeling, writing texts together, and writing texts independently by Class VIII Students of SMP Global Surya, Bandar Lampung, Academic Year 2022/2023. The method used in this research is descriptive qualitative, in the form of a case study. The data source is in the form of text-based reading learning between teachers and students. Data collection techniques were carried out through observation and interviews. The data analysis technique used is the interactive model of analysis developed by Miles and Huberman. The sample in this study was 32 people, who were determined purposively, especially students who had the ability to read and write in the category of having achieved a score above the KKM (minimum completeness criteria). Based on the results of the research and discussion, it can be concluded that the implementation of text-based reading learning can be carried out proportionally. This is indicated by the average achievement of students' reading results in the very good category. Of the 32 students who were used as research subjects, data obtained (1) built contexts of 26 people in the very good category with details, components of "social context" (80.75%), exploration of text characteristics (81.75%), and objectives and text content (81.25%)”; (2) modeling of 26 people (81.25%) with very good category with details, components of "social context" (80.75%), exploration of text features (81.75%), and purpose and content of the text (81 .25%)”; (3) 19 people (59.38%) composed the text together in a sufficient category with details, components "systematics (60.25%), language (59.65%), and content (58.25%)"; and (4) 28 people (87.50%) composed the text independently in a very good category with details, "systematics" components (88.00%), language (86.25%), and content (88.25%)”. Keywords: Learning achievement, text-based reading, and junior high school students